Brentano's Empiricism and the Philosophy of Intentionality. (17th April 2017) - Textor, Mark
Abstract : Brentano's Thesis that intentionality is the mark of the mental is central to analytic philosophy of mind as well as phenomenology. The contemporary discussion assumes that it is a formulation of an analytic definition of the mental. I argue that this assumption is mistaken. According to Brentano, many philosophical concepts can only be elucidated by perceiving their instances because these concepts are abstracted from perception. The concept of the mental is one of these concepts. We need to understand Brentano's Thesis accordingly: It is a piece of advice on how to become introspectively aware of the distinctive feature of mental phenomena. On this understanding of Brentano's Thesis standard objections to it no longer arise.